ANALISIS PENDAPATAN DAN KELAYAKAN USAHATANI KELAPA DALAM DI DESA KASOLOANG KECAMATAN BAMBAIRA KABUPATEN MAMUJU UTARA PROVINSI SULAWESI BARAT - Masse, Abdul; afandi, afandi (AGROTEKBIS, 2017)
Low and fluctuating income of coconut farming systems per land unit area cannot support their farmers to live up to the standard of living. Effort to improve their income could be achieved through increasing the value added of coconut and kopra products sold by the farmers. This study aims to determine the feasibility of coconut farming systemin Kasoloang village Bambaira subdistrict of North Mamuju regency. This research was conducted in June to July 2015. Respondents of 34 coconut farmers were randomly sampled and data collected was analyzed using feasibility and income analysis. The income of the coconut farmers was IDR 6,586,731/ha. The revenue of cost ratio was 2 indicating that the farming system is feasible to be developed. Keywords: Coconut, Feasibility, Income and Kasoloang village.